The nexus of religious behavior and values in Muslim contexts: A systematic literature review - Dahlan, Mohammad Zakaria Drajat; Arif, Moh Zainul; Nadzifah, Ainun; Suladi; Malik, Husni Abdul; Abd. Haris; Darlis; Labib, Muhammad; Erlanda, Julhelmi; Amri, Muhammad; Hudri, Misbah; Ernawati (Research Journal in Advanced Humanities, 2025)
Religious intentions and behaviors constitute a central focus of scholarly inquiry as they bridge internal belief systems and social expressions, shaping the identity, moral values, and everyday practices of Muslims. This study aims to map the research landscape on religious values and behaviors within the Muslim context through a Scopus-based Systematic Literature Review (SLR) covering the period 2010–2025. Employing the PRISMA protocol, 229 documents were identified, analyzed bibliometrically using Bibliometrix R-Packages, and further examined for the substantive contributions of the most influential works. The findings reveal strong publication growth, with an annual increase of 18.95%, and demonstrate an expanding interdisciplinary knowledge base encompassing religion, psychology, health, migration, and business. Collaboration networks highlight two dominant clusters—the United States and Southeast Asia—with the University of Chicago and Malaysian universities emerging as central institutions. Indonesia and the United States are identified as the most productive contributors. Conceptual mapping places religion, Islam, and religiosity as central constructs interlinking themes of identity, acculturation, gender, and mental health. Post-2020 trends emphasize growing attention to mental health, morality, adolescents and young adults, and the psychology of religion. Content analysis of the 15 most impactful articles underscores consistent associations among religious values, religious behaviors, identity, subjective norms, and socio-cultural contexts such as discrimination and acculturation. This study contributes by offering a comprehensive synthesis of the field, identifying key actors, institutions, and research trajectories, and suggesting future agendas that integrate religious identity, norms, and mental health while expanding global perspectives and fostering cross-regional collaboration.